CSR, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL SEBAGAI DETERMINAN MANAJEMEN LABA - Denny Kurnia (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure, leverage, and managerial ownership on earnings management in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The research method used is a quantitative approach with an explanatory design using secondary data in the form of annual reports and corporate sustainability reports. The research sample was selected using a purposive sampling method and resulted in 115 company-year observations after a process of filtering and removing outliers. Data analysis was performed using multiple linear regression with descriptive statistical testing, classical assumption tests, t-tests, F-tests, and coefficients of determination. The results show that CSR disclosure has a negative and significant effect on earnings management, indicating that increasing corporate social transparency can reduce earnings management practices. Leverage has a positive and significant effect on earnings management, indicating that debt pressure can increase the tendency of companies to engage in earnings management. Meanwhile, managerial ownership has no significant effect on earnings management. Simultaneously, CSR disclosure, leverage, and managerial ownership influence earnings management. The conclusion of this study shows that CSR and funding structure are important factors in explaining earnings management practices, while managerial ownership has not been able to become an effective control mechanism in non-cyclical consumer companies in Indonesia. Keywords: Corporate Social Responsibility, Earnings Management, Leverage, Managerial Ownership, Non-Cyclical Consumer Companies